Microbial water quality improvement associated with transitioning from intermittent to continuous water supply in Nagpur, India. (1st August 2021) - Bivins, Aaron; Lowry, Sarah; Wankhede, Sonal; Hajare, Rajashree; Murphy, Heather M.; Borchardt, Mark; Labhasetwar, Pawan; Brown, Joe
Highlights: DEUF and ddPCR allow for sensitive detection of indicators and pathogens in water. Water quality is improved at household taps receiving continuous supply. Nagpur's experience provides key evidence on benefits of continuous water supply. Graphical abstract: Image, graphical abstract Abstract: Nearly half a billion people living in Indian cities receive their drinking water from an intermittent water supply (IWS), which can be associated with degraded water quality and risk of waterborne disease. The municipal water supply in Nagpur, India is transitioning from intermittent to continuous supply in phases. We conducted cross-sectional sampling to compare microbial water quality under IWS and continuous water supply (CWS) in Nagpur. In 2015 and 2017, we collected 146 grab samples and 90 large-volume dead-end ultrafiltration (DEUF) samples (total volume: 6, 925 liters). In addition to measuring traditional water quality parameters, we also assayed DEUF samples by droplet digital PCR (ddPCR) for waterborne pathogen gene targets. At household taps served by IWS, we detected targets from enterotoxigenic E. coli, Shigella spp./enteroinvasive E. coli, norovirus GI and GII, adenovirus A-F, Cryptosporidium spp., and Giardia duodenalis . We observed a significant increase in the proportion of grab samples positive for culturable E. coli (p = 0.0007) and DEUF concentrates positive for waterborne pathogen gene targets (p = 0.0098) at household taps served by IWS compared to those served by CWS. IWS continues to be associated with fecal contamination, and, in this study, with increased prevalence of molecular evidence of waterborne pathogens. These findings add mounting evidence that, despite the presence of piped on premise infrastructure, IWS is less likely to meet the requirements for safely-managed drinking water as defined by the Sustainable Development Goals. Importantly, these findings demonstrate the transition from IWS to CWS in Nagpur is yielding meaningful improvements in microbial water quality.